Blacks in Appalachia - Cabbell, Edward J., 1946-; Turner, William Hobart (Book collections on Project MUSE., 1985)
Blacks in Applalachia focuses needed attetnion on a neglected area of Appalachian studies. Contains a range of contributers such as Carter Woodson and W.E.B. DuBois.